Fast S-parameter Convolution for Eye Diagram Simulations of High-speed Interconnects. - Goh, Patrick; Ain, Mohd Fadzil (2014)
With the increase in signal frequency and the complexity of high-speed interconnects, signal integrity has become a prominent issue in modern electronic devices.